Paradigm Shift: Analyzing Work-Family Conflict Trends with Bibliometric Analysis and Literature Review Highlighting the Future Role’s of Father - Fauziah, Silmi Farhah; Abdullah, Ade Gafar; Widiaty, Isma (Universitas Ahmad Dahlan, 2024)
Work-family conflict (WFC) is an important area of study in the vocational and human resources professions. This article investigates the complex dynamics of work-family conflict, with a particular focus on the developmental role of fathers in balancing professional responsibilities and family duties. This research uses bibliometric analysis methods and literature reviews to analyze the dynamics, research activities, and trends in research topics related to work-family conflict in a more comprehensive namely from 1985 to 2023. This research uses the keywords